A concordância verbal e nominal em escolas públicas e particulares - Amanda Teixeira Pinho Tavares (2021)
This study aims, in the field of sociolinguistics theory, to investigate the phenomenon of subject-verb agreement and noun agreement in writing of Fundamental II students, from public and private schools, in the city of Belo Horizonte. It was assumed that the linguistics variant formed by the presence and absence of agreement is conditioned by groups of linguistic factors (variable linear and relative position of the constituent in the syntagma and textual typology) and not linguistics (level of education, sex, nature of institution and location of schools) – observing the relationship between the uses of language and the linguistic and social factors guiding the variation –, and we still work with the hypothesis that the lack of agreement is the most recurrent variant in the writing of students from public schools and with a lower socioeconomic level. In this analysis, a corpus consisting of 320 wordings and 827 data was used – zero variant. These data were analyzed quantitatively using Rbrul considering the six groups of factors. The results obtained pointed out the relevance of the type of institution, public and private, for the use of the zero variant, favoring the private institutions in the use of the standard variant, as well as the students with a higher social vulnerability presented more favoring the absence of standard agreement. This analysis shows that the Portuguese is changing.